Modalidade Mista de Treinamento (MMT) e Treinamento Resistido (TR): impacto nas alterações do sono, humor, fadiga e cronotipo - Alberto, Tatiane Gomes (2023)
Previous evidence shows that the regular practice of physical activity is essential at any age, whether to prevent disease, promote health or a sense of well-being. This study aimed to evaluate the relationships between Mixed Modality Training MMT-CrossFit® and Resistance Training (RT) with sleep, fatigue, depressive symptoms and chronotype. This is a descriptive, cross-sectional study with a quali-quantitative approach. Clinical, sociodemographic, anthropometric, habits and lifestyle data of 90 CrossFit® and 44 TR practitioners in the city of Fortaleza were evaluated. The instruments used were: Epworth Sleepiness Scale (ESS), Morning-Evening Questionnaire (MEQ), Insomnia Severity Index (IGI), Patient Health Questionnaire (PHQ-9) and Fatigue Severity Scale (FSS). Data were expressed as mean, standard deviation, percentage and absolute values or frequencies, when appropriate. Levene tests were used followed by Student's t test; the Kolmogorov-Smirnov, the Mann-Whitney U test and the Fisher exact test. The significance level was 95% (p<0.05). Data were submitted to IBM SPSS Statistics 22.0 software. The study adhered to the norms of Resolution n.º 466/12 of the CNS. The results revealed that 57.85% of the CrossFit® group were women aged between 18 and 55 years old; and in TR, 52.3% were women, aged between 20 and 55 years. No differences were found regarding gender, age, anthropometric measurements, BMI, WHR, weekly frequency of activity practice, training schedules, alcoholism and smoking habits, as well as clinical data on Systolic and Diastolic Blood Pressure, Heart Rate and Respiratory Rate. There were no differences between groups regarding excessive daytime sleepiness, insomnia, depressive symptoms and chronotype. However, the group that practiced RT showed more fatigue (p=0.01). It was observed that regardless of the sport practiced, the group with afternoon preference had a higher incidence of insomnia (p<0.001) and depressive symptoms (p<0.05). This study emphasizes the importance of considering factors such as sleep, circadian rhythm, fatigue and depressive symptoms when planning changes in habits regarding the adjustment of sports practice schedules, the type of training, its duration and intensity, considering the individual variables of age, gender and chronotype. Such measures aim to optimize performance and ensure a more adequate response from the body to physical exercise, reflecting on better sleep quality, better physical and cognitive performance in exercise and sport.